Clinical profile, management, and outcome of electric burn injuries at a tertiary care hospital - Akram, Bushra; Khalid, Farrukh Aslam; Ishaq, Usman; Ali, Sidra Shumshir; Mehrose, Muhammad Younas; Sajjad, Yawar (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the clinical profile, management and outcomes of electric burn injury cases in a tertiary care setting. Method: The prospective, cross-sectional study was conducted at the Jinnah Burns and Reconstructive Surgery Centre, Lahore, Pakistan, from August 2021 to July 2022, and comprised patients admitted with electric burns. Data collected included demographic variables, total burn surface area, associated injuries, entry and exit points, areas/regions involved, number of blood transfusions, number and type of amputations, total stay in hospital, surgical procedures, and clinical outcomes. The patients were followed up for six months after discharge from hospital. Data was analysed using SPSS 21. Results: Of the 883 patients, 91(10.3%) had electric burns; 70(76.9%) males and 21(23.1%) females. There were 44(48.3%) patients aged 21-40 years and 37(40.6%) were aged >40 years. Total body surface area was >20% in 62(68.2%) patients. Amputation was required in 25(27.5%) cases. The duration of hospital stay was up to 15 days in 50(54.9%) cases. The survival rate was high 88(96.7%). Conclusion: Severe injuries, like high-voltage electrical burns, need interdisciplinary treatment available only in tertiary care settings. Key Words: Electric burn injuries, Electrical injury, Electric burn, Amputation, Electrical flash burn, Burn mortality, Burn epidemiology, Burn reconstruction.